Spatial Variability Of Soil Electrical Conductivity In Relation To Rice Yield For Site-Specific Fertillzer Management - Ganava, EL Taib Saeed Mohamed (2003)
Describing the variability of nutrients status and electrical conductivity (EC) in the paddy soil is essential in developing a variable application rate of fertilizers. The main idea of precision agriculture understands spatial variability of soil properties, crop status and yield within a field; identifying the reasons for yield variability; making farming prescription and crop production management decisions based on variability and local knowledge. Field variability study was carried out in the Tanjung Karang rice irrigation scheme, northwest of Selangor, Malaysia. The general objective of this study was to obtain information about the distribution of soil electrical conductivity, soil nutrients in relation to rice yield to enable site-specific N, P and K fertilizers management in the paddy field. Collection of the soil samples was done at two depths (0-20 and 20-30 cm) using two different schemes from: (i) the small field (a typical 1.2 ha paddy plot), and (ii) a large irrigation compartment (2300 ha). Differential global positioning system (DGPS) was used to locate the sample position.